High-Resolution Computed Tomography of the Inner Ear: Effect of Otosclerosis on Cochlear Aqueduct Dimensions. (August 2019) - Wichova, Helena; Alvi, Sameer; Boatright, Christine; Ledbetter, Luke; Staecker, Hinrich; Lin, James
Objectives: The cochlear aqueduct is a bony duct connecting the scala tympani with the subarachnoid space. Given the pathophysiology of otosclerosis, including bone resorption and new bone deposition, we hypothesize that the cochlear aqueduct in otosclerotic ears is narrowed. Methods: A retrospective review of patients with otosclerosis who have undergone high-resolution computed tomography (HRCT) of the temporal bone was completed. The control cohort included 20 patients with the diagnosis of noise-induced hearing loss, without the diagnosis of otosclerosis. Uniform measurements of cochlear aqueduct dimensions were performed using the axial plane. Results: The otosclerosis cohort included 25 males and 52 females with mean age of 52.2 ± 17.6 years. The control group included 10 males and 10 females with mean age of 64.0 ± 18.5 years. The mean cochlear aqueduct length, width mid canal, aperture base, aperture widest diameter, and funnel diameter in millimeters were 12.19 ± 1.66, 0.68 ± 0.28, 4.21 ± 1.67, 3.23 ± 1.47, and 2.70 ± 1.05 in the ears with otosclerotic foci and 11.57 ± 1.66, 0.69 ± 0.29, 2.56 ± 1.59, 2.77 ± 1.67, and 2.58 ± 1.03 in control group, respectively. Statistical difference was seen in length of cochlear aqueduct, aperture base, and aperture widest diameters ( P = .017, <.001, .007). Conclusions: The length of the cochlear aqueduct and the funnel width are statistically longer in the otosclerotic population compared to control. The width of the cochlear aqueduct is not statistically different.